Bacteriological profile, antibiotic susceptibility and factors associated with neonatal Septicaemia at Kilembe mines hospital, Kasese District Western Uganda - Henry Zamarano (BMC, 2021)
Abstract Introduction Neonatal septicaemia is one of the most common leading causes of neonatal morbidity and mortality in developing countries. It is estimated to affect more than 30 million people worldwide annually, potentially leading to 6 million deaths. Objective(s) To determine the prevalence, bacteriological profile, antibiotic susceptibility and factors associated with neonatal septicaemia among neonates suspected to sepsis at Kilembe mines hospital. Methods We conducted a descriptive cross-sectional study, where purposive sampling technique was used and blood was drawn from 122 neonates suspected to sepsis attending Kilembe Mines Hospital during the period (July to November 2020). Specimens were inoculated in Brain heart infusion broth, transported to Fortportal Regional Referral Hospital, plated daily up to 7 days on blood, chocolate, MacConkey agar and incubated in aerobic and 5% carbondioxide. Pure colonies were identified by Gram stain, biochemical tests and antibiotic sensitivities obtained by Kirby Bauer disc diffusion method. Associations were tested using Chi square with Fisher’s exact or Yates correction tests where necessary and statistical significance was set at P < 0.05. Stata (version 14) used for statistical analysis. Results Blood cultures were positive in 59.0% cases with 55.5% male and 44.4% female. EOS was present in 56.9% and LOS 43.1% of the cases. Gram negative (56.9%) organisms were most implicated with neonatal septicaemia than Gram positives ones (43.1%). Gram positive organisms exhibited better susceptibility to amikacin, linezolid and vancomycin but more resistant to ampicillin and gentamicin. Of the aminoglycosides, amikacin exhibited a verge over netilmicin and gentamicin against Gram negative isolates. Risk factors of neonatal septicaemia were mother’s age of ≥25 years, employed mothers, tertiary-level of education, SVD, ANC attendance of ≥4 times, UTI during pregnancy, PROMS, foul Smelling liquor, urban residence, neonatal birth weight of ≥2500 g, Apgar score 1st and 5th min ≥6 and resuscitation. Conclusion Multi-drug resistant organisms were isolated. Therefore caution is required in selection of antibiotic therapy and avoid empirical treatment.